Detection of sugar solution at low concentration using terahertz spectroscopy combined with frequency-selective surface (FSS) - Ishak, Nurul Syafeeqa (2022)
Terahertz (THz) technology has sparked the interest among researchers to explore the terahertz radiation. However, low detection sensitivity has become the main concern in terahertz spectroscopy in which led to discovery of improvement on limited detection sensitivity by using Frequency Selective Surface (FSS) that provided by the high electric-field concentration in the spatial filtering in FSS. Parametric studies on FSS slot structures, of circular, square, and ring, were explored using CST MICROWAVE STUDIO® software to observe the feasibility of the FSS structures and characterise their performance based on their physical dimensions. Circular slot FSS on the surface of the RT/Duroid® 5880LZ board with thickness of 508 μm showed acceptable results in simulation and measurement despite the limitations of the PCB fabrication. Based on the parametric study of all structures, through surface current intensity on the surface of FSS with or without the FSS showed increase by 20% when the FSS was applied. Next, circular slot FSS was optimised with the utilisation of FSS in material sensing applications towards the molecular resonance of glucose, fructose, and sucrose at THz range resulting the observation at 1.10 THz and 1.98 THz for glucose, 1.29 THz and 1.67 THz for fructose and 1.31 THz and 1.80 THz for sucrose. In this research, electron-beam lithography and chemical etching were used in the microfabrication of FSS on quartz substrate with an aluminium layer due to the limitation of PCB fabrication at THz range and the suitability of microfabrication. Comparing the simulation and measured results of the FSS samples, FSS1 had fair shifts in transmission magnitude by approximately 30% compared with FSS2, which had 50% shifts in transmission magnitude. The focus of this study was to improve the detection sensitivity of terahertz spectroscopy by using FSS for sensing at low concentrations. Therefore, when cascading FSS with the sugar samples, the detection sensitivity at the terahertz range increased by 25% for glucose at 1.98 THz, by 28% for fructose at 1.67 THz, and by 13% for sucrose at 1.80 THz.